DEVELOPMENT OF THE TECHNOLOGY OF THE REINFORCED STEEL OF TYPE (GROUP) BST550 PRODUCTION ACCORDING TO THE AUSTRIAN NORMS IN CONDITIONS OF THE MILL 320 OF RUP "BMZ" - A. V. Rusalenko (Литьë и металлургия)
The developments of production technology of reinforcing steel of type BST550 according to Austrian norms in conditions of the mill 320 of RUP are given.